2017
DOI: 10.1063/1.5017242
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substrate on structural, morphological and optical properties of TiO2 thin films deposited by reaction magnetron sputtering

Abstract: Titanium dioxide (TiO2) films have been prepared by DC reaction magnetron sputtering technique on different substrates (glass, SiO2, platinum electrode-Pt, Silicon-Si). X-ray diffraction (XRD) patterns showed that all TiO2 films were grown along the preferred orientation of (110) plane. Samples on Si and Pt substrates are almost monophasic rutile, however, samples on glass and SiO2 substrates accompanied by a weak anatase structure. Atomic force microscopy (AFM) images revealed uniform grain distribution excep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The vibrational bands of anatase TiO 2 material has centered at 137, 207, 414, 519 and 644.8 cm −1 , respectively, corresponding to the Raman active modes of Eg, Bg, B1g, A1g, and Eg as showed in inserted Fig. 5 [26,27]. It can be concluded that strong anatase peak at 137 cm −1 .…”
Section: Resultsmentioning
confidence: 86%
“…The vibrational bands of anatase TiO 2 material has centered at 137, 207, 414, 519 and 644.8 cm −1 , respectively, corresponding to the Raman active modes of Eg, Bg, B1g, A1g, and Eg as showed in inserted Fig. 5 [26,27]. It can be concluded that strong anatase peak at 137 cm −1 .…”
Section: Resultsmentioning
confidence: 86%
“…The bound state energy level and exciton pair recombination took place in a concise electron-free channel, which may be the cause of the peak at 491 nm. Additionally, the defects in the crystal’s structure caused by oxygen vacancies are another factor in the emergence of this peak in the CuO–Cu 2 O. These oxygen vacancies work as active sites to trap the generated electrons, ultimately enhancing the lifetime of excitons and emphasizing the photocatalytic performance . The broadening of the peaks at 491 nm is caused by the development of mixed nanocrystal phases of CuO and Cu 2 O, which may also be related to the CuO phases .…”
Section: Resultsmentioning
confidence: 99%
“…The growth of TiNPs on glass substrate exhibited greater grain size than that deposited on Si n-type substrate, which agrees with previous research work of Francisco et. al [35]. The Scherrer formula was used to determine the grain size of the titanium thin film (D) [36].…”
Section: Resultsmentioning
confidence: 99%